MYSTICISM ELEMENTS IN THE USE OF FIREARM TECHNOLOGY IN THE MANUSCRIPT ON FIREARMS - Pramono Pramono; Wan Mohd Dasuki Wan Hasbullah; Herry Nur Hidayat (Humaniora, 2015)
In the realm of Malay manuscript researches, the aspect of technology has been given little attention to be researched in a serious and specific manner. Even less is the study focused on the correlation between the Malay technology and Islamic civilization. This article seeks to shed light on the matter and discusses the Malay technology dealing with the use of hand-held firearms which was possibly inherited from the Islamic sources found in the Malay manuscripts. In particular, this article tries to analyse the mysticism elements which seems to be the underlying idea of the indigenous knowledge of firearm technology. The knowledge of such technology and its application are believed to have been practiced by individuals or groups of individuals in the Malay civilization till the 19th mid-century.